Spatial Distribution of Atmospheric Mercury Species in the Southern Ocean. Issue 17 (1st September 2021) - Yue, Fange; Xie, Zhouqing; Yan, Jinpei; Zhang, Yanxu; Jiang, Bei
Abstract: Antarctica and the surrounding Southern Ocean act as an important sink in the global mercury cycle; however, corresponding studies of atmospheric mercury species in these regions are still scarce. Here, we report large‐scale observations of atmospheric gaseous elemental mercury (GEM) and gaseous oxidized mercury (GOM) in the Antarctic marine boundary layer (MBL) taken during a summer cruise. There is large variability in the spatial distribution of GOM, which is likely attributable to the diverse land surface types, including coastal Antarctica, sea‐ice region, and oceanic region, along the cruise route. In coastal Antarctica, the highest GOM level (56.23 ± 47.74 pg·m −3 ) might be attributed to the significant in‐situ oxidation there. Significant in‐situ oxidation of GEM could also occur in the sea‐ice region, causing the significant increase of GOM (up to 87.01 pg·m −3 ), while the uptake of the high content of sea‐salt aerosols in sea‐ice regions might efficiently eliminate GOM in the air, resulting in generally lower content of GOM (13.10 ± 14.48 pg·m −3 ) in the sea‐ice region. In the oceanic region, the lowest level of GOM (3.95 ± 4.69 pg·m −3 ) is due to both the uptake of sea‐salt aerosols and the seasonal melting of first‐year sea‐ice. This study provides insight to understand the mechanisms of the atmospheric mercury cycle in various land surface types in the Antarctic MBL. Key Points: Large spatial variability in gaseous oxidized mercury over different land surface types was observed in the Southern Ocean Low gaseous oxidized mercury content in the sea‐ice region would be to some extent attributed to its greater uptake by sea salt aerosols The seasonal melting of first‐year sea ice can cause a clear decrease in gaseous oxidized mercury levels